Study the partial substitution and annealing on Structure and Electrical Properties of compound Tl2-xAgxSr2-yBayCa2Cu3O10+& Superconductor - Khalid H. Razzeg; Abdul K. Dahash Ali; NIHAD A. Shafeek (Kirkuk Journal of Science, 2015)
We have prepared samples of high temperature superconductors namely Tl2-xAgxSr2-yBayCa2Cu3O10+& using solid state reaction, for different concentration of (x,y=0.1 0.2,0.3, 0.4, 0.5) and compressing by hydraulic at 8 ton/cm2 also annealing samples at 850 0C. The samples have been characterized resistivity measurements using the electrical resistively measurement. At x,y=0.3 ratio of Ag,Ba give a best value of Tc=141 K.The morphology of the samples obtained by AFM in three dimensions views four samples after annealing treatment .Also give a best Nano size value is 94.74 nm at x,y=0.3